2011
DOI: 10.1093/carcin/bgr059
|View full text |Cite
|
Sign up to set email alerts
|

Slit-2 facilitates interaction of P-cadherin with Robo-3 and inhibits cell migration in an oral squamous cell carcinoma cell line

Abstract: Slits are a group of secreted glycoproteins that act as molecular guidance cues in cellular migration. Recently, several studies demonstrated that Slit-2 can operate as candidate tumour suppressor protein in various tissues. In this study, we show Slit-2 expression in basal cell layers of normal oral mucosa colocalized with P-cadherin expression. In contrast, there is a loss of Slit-2 and P-cadherin expression in mucosa of oral squamous cell carcinoma (OSCC). Our in vitro investigations reveal a correlation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…For example, Robo3 is generally associated with neuronal growth cones and interacts with Robo receptors to facilitate axonal pathfinding (49)(50)(51)(52). Although Robo3 also regulates such diverse activities as the migration of cancer cells and the retraction of apical processes in retinal ganglion cells, it remains unclear how it might function in hair-cell progenitors (53,54). Still other molecules, such as that encoded by the highly enriched transcript fndc7, have not yet been assigned a specific function in any system and may represent novel pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Robo3 is generally associated with neuronal growth cones and interacts with Robo receptors to facilitate axonal pathfinding (49)(50)(51)(52). Although Robo3 also regulates such diverse activities as the migration of cancer cells and the retraction of apical processes in retinal ganglion cells, it remains unclear how it might function in hair-cell progenitors (53,54). Still other molecules, such as that encoded by the highly enriched transcript fndc7, have not yet been assigned a specific function in any system and may represent novel pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Analysing the signalling mechanism behind it, they found glycogen-synthase-kinase-3b (GSK-3b) bound to Snail, as well as an increase in activated GSK-3b that phosphorylated Snail leading to its cytoplasmic translocation (Bauer et al, 2009). These same authors also showed that Slit-2, a secreted ECM glycoprotein that acts as a molecular guidance cue in cellular migration, facilitates the interaction of P-cadherin with Robo-3, its receptor, and inhibits cell migration in oral squamous cell carcinoma cell line models (Bauer et al, 2011) (Fig. 4).…”
Section: P-cadherin-downstream Signalling Pathwaysmentioning
confidence: 91%
“…Indeed, in oral epithelial cells that can give rise to oral squamous cell carcinoma, the divergent Robo family member, Robo3, forms a Slit2-induced complex with Pcadherin to regulate migration and intercellular adhesion (Bauer et al 2011). Function blocking antibodies against P-cadherin reduced the secretion of Slit2 by oral epithelia, as well as reduced P-cadherin/Robo3 complex formation (Bauer et al 2011). Complicating matters, a recent study investigating the divergent roles of Robo3 compared to other Robo family members, revealed that Robo3 does not bind tightly to Slit proteins (Zelina et al 2014).…”
Section: Slit-robo Regulation Of Adherens Junctionsmentioning
confidence: 99%